The Effectiveness of P2P Lending Regulation for Customer Protection in Indonesia - Hummerson, Laureen Aurora; Jennifer, Jennifer; Putra, Moody Rizqy Syailendra (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This research discusses Peer-to-Peer Lending  in Indonesia, with a particular focus on the customer protection. With the rapid digitalization of financial technology in Indonesia, P2P lending platforms gain popularity among the society. However, this raises the concern on how effective Indonesia's regulation is on supervising the industry and protecting its users. A  comprehensive  analysis on the current regulatory framework established by the Financial Security Authority (OJK) and Indonesian Fintech Lending Association (AFPI). Identifying the gaps and issues that are risking the protection of the customers.